Default predicted no‐effect target concentrations for antibiotics in the absence of data for the protection against antibiotic resistance and environmental toxicity. (21st February 2022) - Vestel, Jessica; Caldwell, Daniel J.; Tell, Joan; Constantine, Lisa; Häner, Andreas; Hellstern, Jutta; Journel, Romain; Ryan, Jim J.; Swenson, Tim; Xei, Wei
Abstract: The pharmaceutical manufacturing industry, via the AMR Industry Alliance, has developed and implemented steps to help minimize the potential impact of pharmaceutical manufacturing on the spread of antimicrobial resistance (AMR). One of these steps was to publish predicted no‐effect concentrations (PNECs) to serve as targets for antibiotic manufacturing wastewater effluent risk assessments aimed to help protect environmental receptors and to mitigate against the spread of antibiotic resistance. Concentrations below which adverse effects in the environment are not expected to occur (PNECs) were first published in 2018 and are updated annually. The current list now stands at 125 antibiotics; however, it is recognized that this list does not encompass all manufactured antibiotics. Therefore, a statistical evaluation of currently available data was conducted and a default PNEC of 0.05 µg/L for antibiotics in the absence of other data was derived. Integr Environ Assess Manag 2022;18:863–867. © 2022 Merck, Sanofi, Johnson & Johnson Services, Inc, F.Hoffmann‐La Roche Ltd, Teva Pharmaceuticals, GlaxoSmithKline, Novartis Pharma AG, and Pfizer lnc. Integrated Environmental Assessment and Management published by Wiley Periodicals LLC on behalf of Society of Environmental Toxicology & Chemistry (SETAC). Key Points: PNECs were previously published for 125 antibiotics; however, it is recognized that this list does not encompass all manufactured antibiotics. A default PNEC value is necessary in order to provide a target for antibiotics with limited data.